1997
DOI: 10.1111/j.1532-5415.1997.tb03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral White Matter Changes (Leukoaraiosis), Stroke, and Gait Disturbance

Abstract: In our Veteran population, leukoaraiosis is an independent predictor of gait disturbance after accounting for stroke and cerebral atrophy. Although leukoaraiosis is a form of cerebrovascular disease, it appears to be most closely associated to gait disturbance in the absence of symptomatic stroke or leg deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 29 publications
3
36
1
Order By: Relevance
“…Similarly, cerebral SVD are closely related to the development of future stroke, cognitive impairment, or antithrombotic-related fatal complications in the brain. WML is associated with information processing speed and executive function deficits, 23-25 gait disturbance in the elderly, 26 the risk of ischemic and hemorrhagic stroke, 27-29 and anticoagulation-related cerebral 37 CAC is considered a part of subclinical atherosclerosis and the development of CAC is also related to cardiovascular risk factors. 1, 38 Recent progress has further elucidated associations between CAC and the development of atherosclerosis in other vascular beds, such as hypertensive retinopathy, carotid intima-media thickness, peripheral artery disease and early stage nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cerebral SVD are closely related to the development of future stroke, cognitive impairment, or antithrombotic-related fatal complications in the brain. WML is associated with information processing speed and executive function deficits, 23-25 gait disturbance in the elderly, 26 the risk of ischemic and hemorrhagic stroke, 27-29 and anticoagulation-related cerebral 37 CAC is considered a part of subclinical atherosclerosis and the development of CAC is also related to cardiovascular risk factors. 1, 38 Recent progress has further elucidated associations between CAC and the development of atherosclerosis in other vascular beds, such as hypertensive retinopathy, carotid intima-media thickness, peripheral artery disease and early stage nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…All studies found an association between mobility impairment and overall increased WML volumes as well as increased regional WML volumes in periventricular, frontal, parietaloccipital, and frontal periventricular areas. 8,19,23,32,35 Two studies also reported a threshold effect of WMLs on mobility 7,31 with larger volumes of WMLs at baseline found to predict greater declines in mobility over time in longitudinal studies. 27,28,30,38 Finally, it has been reported that a significant increase in WML volumes occurs more frequently in mobility impaired people compared with people without such impairment.…”
Section: Relationship Between Wmls and Mobilitymentioning
confidence: 99%
“…First, the integrity of the neural network within the brain (ie, the corticostriate fibers or thalamostriatal fibers. 31,43 ) and the long descending motor fibers (ie, corticospinal fibers) are crucial in lower extremity motor control, 28 especially in relation to the selection and initiation of movement, direction of movement, and speed and duration of movement. Second, disruption in the frontalsubcortical circuits that interconnect various cortical areas is likely to compromise cognitive performance.…”
Section: Mechanisms To Explain Relationships Between Wmls and Fall Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Leukoaraiosis, or white matter disease (WMD), can be detected as abnormal hypointensities on computed tomography and hyperintesities on T2-weighted or fluid-attenuated inversion recovery magnetic resonance imaging (MRI). 3 A common finding in the elderly, 4,5 WMD has been shown to associate with recurrent stroke, 6,7 cognitive decline, [8][9][10] gait disturbances, 11,12 hemorrhagic transformation, 13 and functional outcome after ischemic stroke. [14][15][16][17] Most studies have examined the relationship between functional stroke outcome and WMD severity using either computed tomography visual scales 14,18,19 or volumetric measurements.…”
mentioning
confidence: 99%